Detection of Cyber Harassment - Asha, P.; Lakshmi Sai Prasanna, A.; Vennela, K. (International Journal of Engineering and Technology, 2018)
Social media usage is increasing day-by-day, besides its uses, many cyber harassment cases are being filed, leaving many adults as victims. It is better to stop these incidents before they happen. This paper main aim is to provide a secure and safe social media environment for its users. Due to some privacy issues and missing of data when deleted it is difficult to find the convict, so timeline posts are considered rather than messages. This paper uses a method semantic enhanced marginalized De-noising auto-encoder for automatic detection of bad posts which prevent them from being posted on the timeline. Whenever a user tries to post something bad in words or sentences, an alert box will be shown that usage of bad words not allowed. This reduces many vulgar posts in the social media. Â